2007
DOI: 10.1007/s00534-006-1139-8
|View full text |Cite
|
Sign up to set email alerts
|

Transgastric pancreatography and EUS-guided drainage of the pancreatic duct

Abstract: Transgastric pancreatography and EUS-guided drainage of the pancreatic duct are reasonable and feasible alternative options for diagnostic and therapeutic management for selected indications (chronic pancreatitis; anomaly of the congenital pancreatic or postoperative gastrointestinal anatomy), with an acceptable periinterventional risk, which broaden the therapeutic spectrum and may avoid surgery but need further evaluation and follow-up investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 13 publications
(44 reference statements)
0
49
1
5
Order By: Relevance
“…However, Will et al noted that during a follow-up period that spanned 4 weeks to 3 years, 29% of patients required surgical intervention [22]. Tessier et al reported stent dysfunction in 55% (20/26) of patients that required a total of 29 repeat endoscopies [7].…”
Section: Technical Success Outcomes and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Will et al noted that during a follow-up period that spanned 4 weeks to 3 years, 29% of patients required surgical intervention [22]. Tessier et al reported stent dysfunction in 55% (20/26) of patients that required a total of 29 repeat endoscopies [7].…”
Section: Technical Success Outcomes and Complicationsmentioning
confidence: 99%
“…These data suggest that patients may benefit from routine stent exchange, particularly if they require prolonged stent duration. [11,13] TP [7] Transluminal (n = 33) 33/36 Bleeding (n = 1) Acute pancreatitis (n = 1) Unspecified mild complication (n = 3) Will et al 2007 [22] Retrograde TP/TA (n = 4) Transluminal (n = 5)…”
Section: Technical Success Outcomes and Complicationsmentioning
confidence: 99%
“…For patient in whom conventional ERCP is not feasible or fails, access and decompression of the main pancreatic duct using EUS-guided pancreatography has increased the success for PD drainage [30][31][32][43][44][45] . This constitutes a minimally invasive alternative to surgery in patient with altered anatomy or severe stone burden not responding to ESWL.…”
Section: Pancreatic Stricturesmentioning
confidence: 99%
“…Matsubayashi Hiroyuki et al Endoscopic ultrasound guided-retrograde pancreatic stent placement … Endoscopy 2013; 45: E435-E436 not performed through the abdominal cavity; hence, it carries a lower risk of pancreatic juice leakage and other complications [5]. This method is worthwhile when attempting to rescue a stenotic pancreatojejunostomy after a Whipple resection.…”
Section: Cases and Techniques Library (Ctl) E435mentioning
confidence: 99%